Indigenous and Non-Indigenous 2021 Unemployment, Employment, and Participation Rates: Improved from 2020 — Education is Critical - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2023)
Unemployment rates were lower, and participation and employment rates were higher for Indigenous and non-Indigenous peoples in Canada in 2021. The meaningful improvements in 2021 are in comparison with the COVID-19-induced negative rates of 2020. The employment and unemployment rates have not fully recovered from their 2019 pre-COVID rates. This is the case for both Indigenous and non-Indigenous peoples. Employment, unemployment, participation, and wage rates are and have been more favourable for non-Indigenous individuals than for Indigenous individuals. When educational levels increase, employment, unemployment, and participation rates improve. Employment measures are examined by gender, age, and education, and Métis and First Nations employment measures are compared.